Reaktualisasi Syari'ah Islam - Zaenul Mahmudi (UIN Maulana Malik Ibrahim Malang, 2006)
As syari'ah, al-Qur'an is one of the sources of Islamic law and the living orientation for Muslim ummah in going through their life. Textual message of Islam (al-Qur'an) had stopped when Muhammad died. In other side, the growing problem is faster than its possible solutions. The problems grow up in line with globalization and information technology that offer some traditions and cultures that meet our different cultures and traditions. We cannot create a new message of al-Qur'an but we can create method of understanding al-Qur'an in nowadays context. We need to use methodological tools from multidiscipline of science in understanding al-Qur'an in order to actualize spirit of al-Qur'an in Indonesian and nowadays context. Reactualizing al-Quran as the core of syari’ah is based on the statement “al-Islam shalih li kull zana wa makan” (Islam is always adaptive toward the dynamic of the era). Accordingly, understanding syari’ah requires the development of methodologies as well as science. Sebagai syari'ah, al-Qur'an adalah salah satu sumber hukum Islam dan orientasi hidup umat Islam dalam menjalani hidup mereka. Pesan tekstual Islam (al-Qur'an) telah berhenti saat Muhammad wafat. Di sisi lain, masalah yang berkembang lebih cepat daripada solusi yang mungkin dilakukannya. Masalahnya tumbuh sejalan dengan globalisasi dan teknologi informasi yang menawarkan beberapa tradisi dan budaya yang sesuai dengan budaya dan tradisi kita yang berbeda. Kita tidak bisa membuat pesan baru al-Qur'an tapi kita bisa menciptakan metode untuk memahami al-Qur'an dalam konteks saat ini. Kita perlu menggunakan alat metodologis dari multidisiplin ilmu dalam memahami al-Qur'an untuk mengaktualisasikan semangat al-Qur'an dalam konteks Indonesia dan saat ini. Reaktualizing al-Quran sebagai inti syari'ah didasarkan pada pernyataan